Influence of Stress Level on the Determination of In Situ Stress by DRA Method - Yuxin Ban; Qiang Xie; Jiahui Tang; Jun Duan; Xiang Fu; Xiaoqiang Xue (Buildings)
Obtaining reliable in situ stress field data is the precondition of the design and excavation of underground engineering. The deformation rate analysis (DRA) method based on the rock deformation memory effect is an effective method for testing in situ stress. Cyclic loading tests were carried out on dense granite to research the influence of stress level on the identification accuracy of the DRA method. The DRA curves of horizontal and longitudinal strains are compared to find the difference between the accuracy in different directions. The results showed that in the range of 15%-60% uniaxial compression strength, the rock deformation memory effect is obvious, which indicates that the DRA method is applicable in low-stress regions, while the measuring accuracy is not as good as that in high-stress areas. When the specimen is subjected to low pre-stress, the accuracy is higher when using the horizontal strain than the longitudinal strain. The accuracy of both horizontal and longitudinal DRA methods increases with the increase in pre-stress. The measuring accuracy is similar when the pre-stress is higher than 45%UCS. What is more, the discrete element numerical model is calculated to verify the test results and reveal the microscopic mechanism of the DRA method under the control of crack evolution. The characteristics of rock memory are related to the evolution of crack closure, cracking, and expansion. The research results can provide an experimental basis for promoting the theoretical development and field application of the testing in situ stress with the DRA method.